PALANGKA RAYA STREET CLOWN LIFE - Lamiang Lamiang; Yesyurun Munthe (Adisam Publisher, 2023)
A street clown is a beggar who earns money in a different way by wearing a clown costume to attract people's attention. The phenomenon of street clowns in Palangkaraya is partly due to the poor economy and the lack of jobs. Street clowning is not only about poverty but also about earning a living. Street clowns range from teenagers to the elderly. The existence of this street clown is an interesting point as a research because this is a social phenomenon that occurs in the midst of society. The problem formulated in this research is what factors influence the presence of street clowns in Palangkaraya city. The research was conducted using descriptive qualitative research method, by conducting observations and interviews. The research was conducted around Yos Sudarso street, Palangka Raya. Based on the analysis of all research data, the factors of the presence of street clowns are family economic factors. The economic factor in question is the responsibility of a person (street clown) in continuing the search for finances for the family, as a result of parents no longer being able to earn money to support life in the family.